News from alternative p38 in cancer and inflammation - Cuenda Méndez, Ana Isabel (My University, 2017)
The aim of our group is both to discover how members of the p38MAPK family regulate cellular function in physiological conditions and in response to environmental stresses, infection and proinflammatory cytokines, and to understand how they become deregulated in several human disease situations such as oncogenic transformation and inflammation. In order to achieve these, our research is focused on: - the discovery of new substrates, interacting proteins and inhibitors for these kinases, and the study of their physiological roles using transgenic mice for the different p38 isoforms; and - the study of p38MAPK as a link between chronic inflammation and cancer, and also as mediators of infection and chronic inflammatory diseases. These studies utilize biochemical, cell biology as well as whole animal model approaches.
Novedades sobre isoformas alternativas de p38 en inflamación y cáncer
Conferenciante invitada al ciclo de conferencias del Máster en Biología Celular y Molecular
Keywords: Cáncer; p38; quinasa; fosforilación; MAPK; señalización celular; inflamación